Baby incubator monitoring system using global system for mobile technology - S, Suthagar; G, Mageshkumar; Tamilsevan, K.S. (Penerbit Universiti Kebangsaan Malaysia, 2022)
Giving birth to a child is one of the precious moments in life. Every second a life is brought into the world and not many children are lucky enough to be healthy. Monitoring the health conditions of a baby in the incubator is a critical medical issue. Many researchers are working in this area to improve the safety of newborn babies. As far as the study that we proceeded with, there exists a fundamental issue in ensuring whether the doctor has attended the emergency or not. In this paper, a system is proposed to monitor the baby inside the incubator using a global system for mobile technology (GSM). The proposed system detects the baby’s temperature, heartbeat, weight, and baby’s sound inside the incubator. If there are any changes in the above-said parameters beyond the threshold level, an intimation will be sent to the concerned doctor through the GSM. The system will keep sending the alert message to the doctor every minute until the doctor acknowledges the baby’s condition. This system will enhance the safety of newborn babies by addressing the above-said issue, thereby reducing the risk involved in monitoring the babies inside the incubator. A prototype is developed and it was tested for functional verification.